Comparison of the cytotoxic, genotoxic and apoptotic effects of Sugammadex and Neostigmine on human embryonic renal cell (HEK-293) - Büyükfırat, Evren; Koyuncu, ć°smail; Karahan, Mahmut Alp; Binici, Orhan; Altay, Nuray; Kirmit, Adnan; Gönel, Ataman (Cellular and Molecular Biology, 2018)
Acetylcholinesterase inhibitors, including Neostigmine, have been used to reverse neuromuscular blockage for many years. Sugammadex reverses this blockage using its gamma cyclodextrin ring, a mechanism that differs from that of cholinesterases and so circumvents the side effects of Neostigmine. Although the superiority of Sugammadex to Neostigmine has been outlined in several clinical studies, to our knowledge, there is not any research into cell culture that compares the cytotoxic, genotoxic and apoptotic effects of the two drugs. Hence, this is the first study to compare the cytotoxic, genotoxic and apoptotic effects of different dosages of both drugs on human embryonic renal (HEK-293) cells. In this study, the cytotoxicity, genotoxicity and apoptotic effects of Sugammadex and Neostigmine on HEK-293 cells were analyzed with using the MTT, Comet Assay and Flow Cytometric Annexin-V methods, respectively. The results demonstrate that Neostigmine at 50, 100, 250, and 500 µg/mL is more cytotoxic than equivalent dosages of Sugammadex. Neostigmine at 500 and 1000 µg/mL was found to be more genotoxic, and Neostigmine at 500 µg/mL had a statistically higher risk of causing apoptosis and necrosis than Sugammadex (p<0.05). Neostigmine administered in-vitro in the same doses as Sugammadex had greater cytotoxic, genotoxic and apoptotic effects on HEK-293 cells.